An Irreversible Effect of Response Cost on Human Fixed-Interval Responding. - Okouchi, Hiroto (Psychological Record, 2024)
Two experiments were conducted to examine the effects of point-loss response cost on the responding under fixed-interval (FI) schedules in humans. Responses by undergraduates produced points exchangeable for money arranged according to an FI 90-s schedule (Experiment 1) or a multiple FI 30-s FI 60-s FI 90-s schedule (Experiment 2). Following this baseline, a contingency of response cost, under which responses lost points, was introduced then withdrawn. Response rates with the response cost were lower than those during the baseline. Following termination of the response cost contingency, the final response rates were again lower than those during the baseline (Experiments 1 and 2). Such low-rate responding was not found for participants who were exposed only to no-cost FI schedules (Experiment 2). These results demonstrate an irreversible effect of response cost. Generality and implications of the findings were discussed in the context of the research in punishment and human schedule performance.